A biblioteca universitária e a pessoa com deficiência: recomendações de acessibilidade para o SISTEBIB/UFAM - Ferreira, Rafael Lima Medeiros (2019)
This study intends to propose a model of institutional policy that allows the person with disabilities access to the information products and services offered by the Libraries System of the Federal University of Amazonas (SISTEBIB/UFAM). This is a qualitative research, descriptive and exploratory in nature, cut transversally, where a total of 58 servers were filled in SISTEBIB/UFAM. A participant observation and interview was used for the data collection that resulted in a self-evaluation of SISTEBIB/UFAM about its accessible character. The theoretical reference was sought in books, periodicals and databases, authors were sought to raise discussions about the importance of reducing barriers so that the person with disabilities can enjoy the instruments available in society. The present recommendations, based on the rationalist and argumentative approaches to the analysis and evaluation of public policies, seek to offer university libraries, here represented by SISTEBIB/UFAM, the opportunity to transform their products and information services that are adequate and accessible to the demands of information and knowledge of the disabled person as a user.